Aurora - Masa Sayegh; Masa Zablah (My University, 2024)
In this generation, the need for online shopping in the beauty industry is rising, and the majority of women, regardless of age, are interested in beauty products. However, they often struggle with choosing the best sources that provide reliable international brands with affordable prices. Our project objective is to provide a convenient and personalised shopping experience for users and offer sellers a platform to reach a wider audience and manage their products effectively. It aims to develop a comprehensive e-commerce platform for selling makeup and skincare products. The platform includes a user-friendly application and website with distinct categories for makeup and skincare products. Users can register and create an account, enabling them to track their purchases. They can easily search for products, view detailed descriptions, and prices. They can save, like, and add products to their shopping cart and specify quantities for purchase. The checkout process is streamlined, allowing users to make purchases using VISA, or cash on delivery. After purchasing, users can rate products and provide feedback, enhancing the community's shopping experience. For skincare products. The platform also provides notifications for sales, keeping users informed about discounts. Additionally, users who make purchases totaling over a certain amount will receive a discount, encouraging repeat purchases and customer loyalty. Administrators have full control over the platform, being able to add new products, manage inventory, and upload sales information. After some research, we discovered that while there are a lot of beauty platforms available globally, there aren't many in our country and none that provide products from global brands. There are some social media platforms where you need to make orders on direct messages, and the procedure is time-consuming and costly.